2017
DOI: 10.1016/j.toxlet.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

The tumor suppressor phosphatase and tensin homolog protein (PTEN) is negatively regulated by NF-κb p50 homodimers and involves histone 3 methylation/deacetylation in UROtsa cells chronically exposed to monomethylarsonous acid

Abstract: UROtsa cells have been accepted as a model to study carcinogenicity mechanisms of arsenic-associated human bladder cancer. In vitro continuous exposure to monomethylarsonous acid (MMA), leads UROtsa cells to commit to malignant transformation. In this process, NF-κβ-associated inflammatory response seems to play an important role since this transcription factor activates some minutes after cells are exposed in vitro to MMA and keeps activated during the cellular malignant transformation. It is known that a sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Interestingly, a recent study using the immortalized cell line of human urothelial cells (UROtsa), a well-established model to study carcinogenesis mechanisms of human bladder cancer, revealed that monomethylarsonous acid (MMAIII)-induced NF-kB activation modulates PTEN expression. Moreover, NF-kB subunit p50 binding to PTEN promoter is associated with decreased PTEN expression [39]. Our current work further enriches the regulatory network of NF-kB signaling for the post-transcriptional modulation of PTEN (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…Interestingly, a recent study using the immortalized cell line of human urothelial cells (UROtsa), a well-established model to study carcinogenesis mechanisms of human bladder cancer, revealed that monomethylarsonous acid (MMAIII)-induced NF-kB activation modulates PTEN expression. Moreover, NF-kB subunit p50 binding to PTEN promoter is associated with decreased PTEN expression [39]. Our current work further enriches the regulatory network of NF-kB signaling for the post-transcriptional modulation of PTEN (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…Existing evidence also showed that PTEN is a potent tumor suppressor and down-regulated PTEN enhances cell proliferation and invasion in liver cancer [25]. Previous study also revealed that PTEN is correlated with histone modifications [16,17]. A study performed in breast cancer stem cells provides the evidence that HDAC7 can regulate histone 3 lysine 27 acetylation [13].…”
Section: Discussionmentioning
confidence: 95%
“…Previous study has reported that PTEN is involved in the progression of liver cancer and might be involved in the stemness of cancer stem cells [14,15]. Several studies have provided evidence that PTEN is correlated with histone modifications [16,17]. However, the roles of miR-342-3p, HDAC7 and PTEN in LCSC remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In B cells, the absence of PTEN showed an increased in NF-κB activity after TLR4 stimulation [ 56 ]. Additionally NF-κB negatively regulate PTEN [ 57 , 58 ]. Accordingly, in the classical subtype, loss of PTEN may also be implicated in tumor cell proliferation through TLR canonical activation ( Fig 5 ).…”
Section: Discussionmentioning
confidence: 99%